Cloud microphysical properties at Arctic atmospheric observatories: Eureka, Canada - Matthew Shupe (Arctic Data Center, 2016)
This data set contains cloud microphysical properties data for Eureka, Canada. Cloud microphysical properties determine the manner in which clouds impact atmospheric radiation and the hydrological cycle. This collection of data sets documents vertically-resolved cloud microphysical properties at multiple locations across the Arctic. Observations are based on the available surface-based, remote-sensors measurements at each site. A variety of cloud microphysics retrieval algorithms are employed to first identify the cloud type (phase) and then characterize the hydrometeor characteristic size and water content for both liquid and ice phases. While an attempt has been made to maintain consistent retrievals across the different observatories, each has a unique set of cloud observation instruments which can impose unique, site-specific signatures on the retrieval results.